EXTH-03. COMBINED TOP1 AND PARP INHIBITION ENFORCES GENOMIC INSTABILITY AND CELL DEATH IN PTEN-DEFICIENT GLIOBLASTOMA. (12th November 2021) - Kim, Olga; Butler, Madison; Pang, Ying; Yu, Guangyang; Merchant, Mythili; Ranjan, Alice; Gilbert, Mark; Pommier, Yves; Wu, Jing
Abstract: BACKGROUND: Glioblastoma is an aggressive brain tumor with high mortality. The development of new therapies is critical for improving patient outcomes. LMP400, a novel topoisomerase I (TOP1) inhibitor, traps TOP1 cleavage complexes, thereby generating DNA damage. Poly(ADP-ribose) polymerase (PARP) is involved in DNA repair responses triggered by TOP1 inhibition. Niraparib is a potent PARP inhibitor that can cross the blood-brain barrier. Loss of phosphatase and tensin homolog (PTEN) occurs in 40% of GBM patients and is known to promote DNA damage repair deficiency. Here, we hypothesize that PTEN loss presents a vulnerability to a combined induction of DNA damage and inhibition of repair mechanisms. METHODS: Human glioblastoma cells (U251, SNB-75, SF-295, LN18) and patient-derived glioblastoma stem cells (GSC923 and GSC827) were treated with LMP400 and/or Niraparib. Cell viability and apoptosis were examined using Celigo image cytometer and Annexin V/PI assay at 72h after treatment. Single clones after PTEN knockdown using shRNA were isolated after puromycin selection. For planned studies of PTEN knockout, sgRNA plasmids targeting PTEN will be transiently transfected and GFP-positive single KO clones will be isolated. PTEN will be restored in PTEN-null cells using lentiviral transduction. RESULTS: CRISPR-Cas9 KO screening in GSC923 cells suggests that LMP400 is unlikely a substrate for ABC transporters. LMP400 and Niraparib synergistically induced cytotoxic effects in U251, SF-295, GSC923, GSC827 cells lacking PTEN expression. Combined LMP400/Niraparib led to increased expression of gamma-H2AX, cleaved caspase 3 and PARP, indicative of enhanced DNA damage and cell death. CONCLUSION: LMP400 and Niraparib act synergistically to target PTEN-deficient glioblastoma by inducing DNA damage and cell death. These results will be further verified in isogenic cells in vitro as well as in vivo in a mouse model driven by PTEN deletion which would strongly support a novel therapeutic strategy in a subset of glioblastoma with PTEN loss.